Pathways from poverty : the process of graduation in rural Bangladesh - Orr, Alastair; Poverty Elimination through Rice Research Assistance (Project) (Dhaka : The University Press, 2009)
Research commissioned by Poverty Elimination through Rice Research Assistance (Project)
Includes bibliographical references and index.
Keywords: Rural poor -- Bangladesh -- Case studies; People with social disabilities -- Bangladesh -- Economic conditions -- Case studies; Poverty -- Bangladesh -- Case studies; Rural development -- Bangladesh -- Case studies